MENGENAL SISTEM PENERANGAN LABORATORIUM/LIS - Prihatini Prihatini (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
Clinical laboratory as a supporting tool to establish diagnostic as well as the efficiency of laboratory results will need on time report,accurate result, and satisfaction of the customer should necessary supported by suitability equipments. Most laboratories using automaticmachine need the assistance of LIS (Laboratory Information System) to enhance good results. To prepare its ready use of these laboratoryinstruments, request orders of the physicians’ should be explicit and content satisfaction of the clinically symptoms as well. The laboratorypersonnel and the supervisor of LIS software should know well how to operate it to match with the other laboratory equipment used.The result of laboratory’s orders should be recorded by LIS and send back to the physicians. In this computerisation world, automationof clinical laboratory is necessary if efficient results are the main need.